PRODUCTIVE WAQF FOR RURAL COMMUNITY EMPOWERMENT: A COMMUNITY-BASED DEVELOPMENT PERSPECTIVE - Eka Ayuningtyas; Hans Aulia Utama Hasibuan (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
Community-Based Development (CBD) positions local communities as the primary actors in development, but limited capital, institutional capacity, and access to technology are key obstacles in rural areas. This article examines how productive agricultural waqf can serve as an alternative financing mechanism that integrates CBD principles with government support (Community Initiatives Government Support) and community empowerment governance within a regional unit. The case study is the Premium Melon Greenhouse Cluster project in Gunungkidul Waqf City, Yogyakarta Special Region. Using a descriptive qualitative approach with actor ecosystem analysis, this study demonstrates that the project successfully integrates community governance: nazhir, sharia crowdfunding through the Satu Wakaf Marketplace platform, and government regulatory support in Gunungkidul Regency. The utilization of Village Funds, Corporate Social Responsibility (CSR) combined with productive waqf can create a blended finance model that integrates stakeholders. This research contributes to demonstrating that productive waqf can serve as an instrument for community empowerment.